EFEKTIVITAS RETRIBUSI PASAR DALAMMENINGKATKAN PENDAPATAN ASLI DAERAH DI KABUPATEN GORONTALO - Abjul, Riswan; Machmud, Joice; Paramata, Sri Hantsuti (Program Studi Akuntansi, 2019)
The objective of this research is to describe the effectiveness of market retribution in increasing original local government revenue of Gorontalo Regency. This research is quantitative research which guided by the data provided by the relevant office. The scope of this research includes the amount of original local government revenue and amount of market retribution received at Gorontalo regency in 2013 until 2017. The result showed effectiveness of market retribution on orginal local government revenue in 2013 are 135%, in 2014 are 105,22%, in 2015 are 82,51%, in 2016 are 89,93%, and 2017 are 71,63%. Based on effectiveness criteria that used showed market retribution is classsifiet as effective. But has not been able to give a significant influence on original local government revenue at Gorontalo regency, because number of targets and realization of market retribution that set by government decreases every years.